Backwörks : Our Line Of Very Expensive Merchandise - Moore, Barbara; Hendricks, Jon (New York : Backworks, 1978)
Newspaper print, 43 x 29 cm. Folded, 8 pages. Illustrated in black & white. Rare catalogue with works created by artists usually associated with Fluxus. Through her bookshop Backworks, founded in 1976 and co-owned with Jon Hendricks, Barbara Moore has been a seminal and innovative champion of artists working in alternative mediums. In the 1970's she curated the first Fluxus exhibition in New York and the first exhibition of Dieter Roth's artists' books in the United States. Since then she has presented exhibitions, often with artists'-book catalogues, of work by Lawrence Weiner, George Maciunas, Henry Flynt, Ken Dewey, Charlotte Moorman, Mel Bochner, Mimi Smith, Yvonne Rainer, Peter Moore, Buster Cleveland, Davi Det Hompson and many others. Under the name ReFlux Editions, she continued publication of classic Fluxus publications originally produced by George Maciunas.
Filliou, Robert ; Spoerri, Daniel ; Brecht, George ; Byars, James Lee ; Cage, John ; Grooms, Red ; Hansen, Al ; Hyde, Scott ; Johnson, Ray ; Jones, Joe ; Kaprow, Allan ; Knowles, Alison ; Ono, Yoko ; Patterson, Ben ; Saito, Takako ; Sissor, Bros.
Engels
boek